Identifying Pathways and Networks Associated With the SARS-CoV-2 Cell Receptor ACE2 Based on Gene Expression Profiles in Normal and SARS-CoV-2-Infected Human Tissues - Feng, Qiushi; Li, Lin; Wang, Xiaosheng (Frontiers in Molecular Biosciences, 2020)
Because ACE2 is a host cell receptor of the SARS-CoV-2, an investigation of ACE2 expression in normal and virus-infected human tissues is crucial for understanding the mechanism of SARS-CoV-2 infection. We identified pathways associated with ACE2 expression and gene co-expression networks of ACE2 in pan-tissue based on the gene expression profiles in normal human tissues. We found that the pathways significantly associated with ACE2 upregulation were mainly involved in immune, stromal signature, metabolism, cell growth and proliferation, and cancer and other diseases. The number of genes having a significant positive expression correlation with ACE2 in females far exceeded that in males. The estrogen receptors (ESR1 and ESR2) and androgen receptor (AR) genes had a significant positive expression correlation with ACE2. Meanwhile, the enrichment levels of immune cells were positively associated with the expression levels of ESR1 and ESR2, while they were inversely associated with the expression levels of AR in pan-tissue and multiple individual tissues. It suggests that females are likely to have a more robust immune defense system against SARS-CoV-2 than males. ACE2 was upregulated in SARS-CoV-2-infected tissues relative to normal tissues and in SARS-CoV-2-infected males relative to females, while its expression levels had no significant difference between healthy females and males. Numerous immune-related pathways were highly enriched in SARS-CoV-2-infected males relative to females. These data indicate that males are more susceptible and more likely to have an excessive immune response to SARS-CoV-2 infection than females. This study furnishes potentially cues explaining why females have better clinical outcomes of SARS-CoV-2 infections than males and warrant further investigation for understanding the mechanism of SARS-CoV-2 infection.